Contestation and Representation Claims - Maharani, Fidiara (PCD Journal, 2024)
Theory of "the representative claim" opens up the political space of representation beyond the formal realm, and contestation over representation can take place both in the electoral and non-electoral arena. This contestation takes the form of narrative claims to justify and legitimize the representation carried out on the claimed constituents. This research analyzes the contestation between the NGOs who facilitate the Anak Dalam Tribe Indigenous Community (Suku Anak Dalam, or SAD) as a non-electoral representation actor in the alleged conflict between the SAD Indigenous Community and one of the palm oil companies in Jambi Province. Using a qualitative approach to obtain depth of data and analysis, this research shows that in the contestation of claims between companion groups, at least three claims are produced, namely representation claims, misrepresentation claims, and representation claims of interests or values. Contesting claims center on differences in views regarding the best way to improve the welfare of the SAD Indigenous Peoples. This claim itself produces various responses of acceptance and rejection by the constituents – the SAD Community – which the companion group claims to be the group they represent.